2006
DOI: 10.1152/ajpendo.00510.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calpain results in impaired contraction-stimulated GLUT4 translocation in skeletal muscle

Abstract: It was previously found that transgenic mice that overexpress the calpain inhibitor calpastatin (CsTg) have an ϳ3-fold increase in GLUT4 protein in their skeletal muscles. Despite the increase in GLUT4, which appears to be due to inhibition of its proteolysis by calpain, insulin-stimulated glucose transport is not increased in CsTg muscles. PKB (Akt) protein level is reduced ϳ60% in CsTg muscles, suggesting a possible mechanism for the relative insulin resistance. Muscle contractions stimulate glucose transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
2
14
1
Order By: Relevance
“…4). In light of reports suggesting that CaMKII might be a substrate of the Ca 2ϩ -activated protease calpain (12,25), we examined the effects of glucosamine and PUGNAc on the cleavage of ␣-fodrin, a well-characterized target for calpain (41). Consistent with these reports, we found that the cleaved 145/ 150-kDa fragment of ␣-fodrin was significantly increased during I/R compared with normoxic perfusion.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…4). In light of reports suggesting that CaMKII might be a substrate of the Ca 2ϩ -activated protease calpain (12,25), we examined the effects of glucosamine and PUGNAc on the cleavage of ␣-fodrin, a well-characterized target for calpain (41). Consistent with these reports, we found that the cleaved 145/ 150-kDa fragment of ␣-fodrin was significantly increased during I/R compared with normoxic perfusion.…”
Section: Discussionsupporting
confidence: 69%
“…4, A and B). Otani et al (25) recently suggested that CaMKII might be a target for the Ca 2ϩ -sensitive cysteine protease calpain. This raises the possibility that the loss of total CaMKII seen here might be a consequence of calpain-mediated proteolysis and that the protection seen with glucosamine and PUGNAc could be due to attenuation of calpain activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach ignores the fact that genes are expressed as proteins and that gene expression can be regulated at a number of steps during translation as well as posttranslationally. As an example of posttranslational regulation, it has been shown that overexpression of calpastatin, the endogenous inhibitor of the protease calpain, results in large increases in expression of GLUT4, CAMKII, and AMPK proteins despite a decrease or no change in their mRNA levels (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study investigated the effect of the insulin signaling-independent muscle contraction-stimulated glucose transport in transgenic mice that overexpress the calpain inhibitor calpastatin. Despite a threeto fourfold increase in glucose transporter-4 protein, calcium calmodulin kinase II and AMP kinase in their skeletal muscles, contraction-stimulated glucose transporter-4 translocation, and glucose transport were not increased above wild type values (Otani et al 2006). These findings also suggest that the inhibition of calpain results in alterations of a step downstream of the insulin signaling pathways and/or at the level of the final effector system itself.…”
Section: Discussionmentioning
confidence: 76%